A Multicenter Pharmacosurveillance Study for the Evaluation of the Efficacy and Safety of Recombinant Factor VIII in the Treatment of Patients with Hemophilia A - Aygören-Pürsün, Emel; Scharrer, Inge; German Kogenate Study Group (Thrombosis and Haemostasis, 1997)
In this open multicenter study the safety and efficacy of recombinant factor VIII (rFVIII) was assessed in 39 previously treated patients with hemophilia A (factor VIII basal activity ≤15%).Recombinant FVIII was administered for prophylaxis and treatment of bleeding episodes and for surgical procedures. A total of 3679 infusions of rFVIII were given. Efficacy of rFVIII as assessed by subjective evaluation of response to infusion and mean annual consumption of rFVIII was comparable to that of plasma derived FVIII concentrates. The incremental recovery of FVIII (2.4 ± 0,83%/IU/kg, 2.12 ± 0.61%/IU/kg, resp.) was within the expected range. No clinical significant FVIII inhibitor was detected in this trial. Five of 16 susceptible patients showed a seroconversion for parvovirus B19. However, the results are ambiguous in two cases and might be explained otherwise in one further case. Thus, in two patients a reliable seroconversion for parvovirus B19 was observed.